Diagnostic accuracy of TIMI versus GRACE score for prediction of death in patients presenting with Acute Non-ST Elevation Myocardial Infarction (NSTEMI) - Naqvi, Syed Haseeb Raza; Abbas, Tariq; Tun, Han Naung; Naqvi, Ali Ahmad; Zaffar, Zubair; Gill, Badar ul Ahad; Ahmad, Nisar (Journal of Cardiology and Cardiovascular Medicine, 2019)
Background: Acute Coronary Syndrome describes a spectrum of disease ranging from unstable angina through non-ST-Elevation Myocardial Infarction (NSTEMI) to ST-Elevation Myocardial Infarction (STEMI). Early death in NSTEMI is usually due to an arrhythmia. Patients should be admitted immediately to hospital, preferably to a cardiac care unit because there is a significant risk of death. Objective: To compare the diagnostic accuracy of TIMI versus GRACE for prediction of death in patients presenting with Acute Non-ST elevation Myocardial Infarction. Material & Methods: This present cross sectional study was conducted at Department of Cardiology, CPEIC, Multan. All patients assessed according to given scores in the two scoring system i.e. TIMI risk score and GRACE score. Then patients were labeled as high or low risk for death. Data was collected by using pre-designed proforma. 2x2 tables were generated to measure the sensitivity, specificity, positive predictive value, negative Predictive value and diagnostic accuracy of TMI Risk score and GRACE Score for prediction of death in NSTEMI patients. Results: In our study the mean age of the patients was 55.73±9.78 years. The male to female ratio of the patients was 1.6:1. The diabetes as risk factor was found in 145(39%) patients, smoking as risk factor was found in 53(14.2%) patients and hypertension as risk factor was found in 174(46.8%) patients. the sensitivity of TIMI risk was 97.7% with specificity of 92.93% and the diagnostic accuracy was 95.16%, similarly the sensitivity of GRACE risk was 100% with specificity of 95.96% and the diagnostic accuracy was 97.85%. Conclusion: Our study results concluded that both the TIMI risk and GRACE risk are good predictor of death in patients presenting with Acute Non-ST elevation Myocardial Infarction with higher sensitivity and diagnostic accuracy. However the GRACE risk showed more accurate results as compared to TIMI risk.